2004
DOI: 10.1523/jneurosci.0684-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Localization of a Specific Large-Conductance Calcium-Activated Potassium Channel Subtype Controls Compartmentalized Ethanol Sensitivity in the Nucleus Accumbens

Abstract: Alcohol is an addictive drug that targets a variety of ion channels and receptors. To address whether the effects of alcohol are compartment specific (soma vs dendrite), we examined the effects of ethanol (EtOH) on large-conductance calcium-activated potassium channels (BK) in cell bodies and dendrites of freshly isolated neurons from the rat nucleus accumbens (NAcc), a region known to be critical for the development of addiction. Compartment-specific drug action was indeed observed. Clinically relevant concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(124 citation statements)
references
References 62 publications
3
121
0
Order By: Relevance
“…50 mM EtOH, a concentration known to strongly influence channel activity (19), increased ␣␤4 BK channel open probability ( Fig. 1A; middle trace EtOH 3 min) compared to control (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…50 mM EtOH, a concentration known to strongly influence channel activity (19), increased ␣␤4 BK channel open probability ( Fig. 1A; middle trace EtOH 3 min) compared to control (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, we also reported that EtOH effects depend on BK channel subunit composition in ventral striatum. We found that ␣␤4 BK channels were potentiated by EtOH, whereas ␣␤1 channels were not (19). In the present study, we tested the hypothesis that BK subunit composition can control the degree and duration of ethanol sensitivity and, because of robust expression in striatum-a brain region implicated in addiction-we predicted that differences in BK subunit expression can translate into altered ethanolinduced behaviors.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…For example, ethanol decreases the excitability of neurons in rat dorsal root ganglia by activating the BK Ca channel, and this is associated with ethanol-related analgesia [44]. In rat nucleus accumbens neurons, ethanol accelerates the action potential repolarization by activating the BK Ca channel [45]. In cultured human umbilical vein endothelial cells, 10 and 50 mmol/L ethanol directly activate BK Ca channels, leading to increased endothelial proliferation, indicating a possible beneficial effect of ethanol on endothelial function [20].…”
Section: Mechanism Of Activation Of the Bk Ca Channel By Which Etoh-pmentioning
confidence: 99%
“…Further open questions are the interesting connection of alcohol actions with the adenosine receptors (Dar et al, 1983;Choi et al, 2004;Dar, 2006), protein kinases (Hodge et al, 1999;Proctor et al, 2003;Wallace et al, 2007), NMDA and AMPA receptors (Lovinger et al, 1989;Woodward, 2000), BK channels (Martin et al, 2004;Cowmeadow et al, 2006), glycine receptors (Davies et al, 2003), K v + channels (Espinosa et al, 2001), and the modulation of alcohol actions via G protein-coupled receptors (Wan et al, 1996;Nie et al, 2004;Besheer et al, 2006) as well as the molecular mechanism behind of the fascinating observation of behavioral alcohol antagonism by pressure (Alkana et al, 1985;Davies and Alkana, 2001). The challenge is to find answers to these and many more important questions in the future and to integrate these findings into an increasingly comprehensive picture on which the majority of us can agree.…”
Section: Summary Open Questions and Future Developments And Apparentmentioning
confidence: 99%